Willow grouse autosomal consensus sequence - Kozma, Radoslav; Melsted, Páll; Magnússon, Kristinn P.; Höglund, Jacob (Dryad Digital Repository, 2015)
Willow grouse autosomal consensus sequence used as input for PSMC. The file was generated from a filtered bam file using the samtools mpileup, bcftools and vcfutils.pl (vcf2fq) pipeline (downgrading mapping quality for reads containing excessive mismatches (-C) to 50, minimum read depth (-d) set to 1/3 of the mean genome coverage (22) and maximum read depth (-D) set to twice the mean genome coverage (136)). All non-autosomal sites were discarded.